Hyperhomocysteinemia and Venous Thrombosis: A Meta-analysis - Heijer, Martin den; Rosendaal, Frits R.; Blom, Henk J.; Gerrits, Wim B. J.; Bos, Gerard M. J. (Thrombosis and Haemostasis, 1998)
Hyperhomocysteinemia is an established risk factor for atherosclerosis and vascular disease. Until the early nineties the relationship with venous thrombosis was controversial. At this moment ten case-control studies on venous thrombosis are published. We performed a meta-analysis of these reports.We performed a MEDLINE-search from 1984 through June 1997 on the keywords “homocysteine” or “hyperhomocysteinemia” and “venous thrombosis”, which yielded ten eligible case-control studies.We found a pooled estimate of the odds ratio of 2.5 (95% CI 1.8-3.5) for a fasting plasma homocysteine concentration above the 95th percentile or mean plus two standard deviations calculated from the distribution of the respective control groups. For the post-methionine increase in homocysteine concentration we found a pooled estimate of 2.6 (95% CI 1.6-4.4).These data from case-control studies support hyperhomocysteinemia as a risk factor for venous thrombosis. Further research should focus on the pathophysiology of this relationship and on the clinical effects of reducing homocysteine levels by vitamin supplementation.